2007
DOI: 10.1111/j.1600-0714.2007.00559.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of functional gene polymorphisms: IL‐1B, IL‐6 and TNFA in benign migratory glossitis in Brazilian individuals

Abstract: Our findings demonstrate that the polymorphism +3954 IL-1B is associated with an increased risk of BMG development and suggest a genetic basis for disease development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 36 publications
2
21
0
2
Order By: Relevance
“…DNA was extracted from epithelial buccal cells using sequential phenol and chlorophorm extraction procedures and precipitated with salt/ethanol solution (6.0 m GuSCN, 65 m m Tris‐HCL, with 450 μL 70% ethanol) (19). For genotyping TNFA −308, DNA fragments were amplified by use of the following primer pair: 5′‐AGGCAATAGGTTTTGAGGGCCAT‐3′ and 5′‐TCCTCCCTGCTCCGATTCCG‐3′ (19). The polymerase chain reaction (PCR) was performed in a 25‐μL reaction mixture containing PCR buffer (Promega Corporation, Madison, Wisconsin, USA), 2.5 m m MgCl 2 , 10 m m dNTPs, 100 n m each primer, 200 ng of sample DNA and 2 U Taq polymerase.…”
Section: Methodsmentioning
confidence: 99%
“…DNA was extracted from epithelial buccal cells using sequential phenol and chlorophorm extraction procedures and precipitated with salt/ethanol solution (6.0 m GuSCN, 65 m m Tris‐HCL, with 450 μL 70% ethanol) (19). For genotyping TNFA −308, DNA fragments were amplified by use of the following primer pair: 5′‐AGGCAATAGGTTTTGAGGGCCAT‐3′ and 5′‐TCCTCCCTGCTCCGATTCCG‐3′ (19). The polymerase chain reaction (PCR) was performed in a 25‐μL reaction mixture containing PCR buffer (Promega Corporation, Madison, Wisconsin, USA), 2.5 m m MgCl 2 , 10 m m dNTPs, 100 n m each primer, 200 ng of sample DNA and 2 U Taq polymerase.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that polymorphisms of cytokines have been associated with risk of oral mucosal disease (Bazrafshani et al, 2002;Bai et al, 2007;Xavier et al, 2007;Guimarães et al, 2007a;Kalkan et al, 2013). Kalkan et al (2013) reported that intron 3 VNTR polymorphism in the IL-4 gene plays an important role in the development of recurrent aphthous stomatitis in the Turkish population.…”
Section: Discussionmentioning
confidence: 99%
“…Xavier et al (2007) reported that IL-6 and TNF-α gene polymorphisms are associated with occurrence of oral lichen planus. For ROU, Guimarães et al (2007a) reported that polymorphism of high IL-1β production was correlated with an increased risk of ROU. IL-6 gene polymorphisms can increase susceptibility to ROU (Bazrafshani et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of functional genetic polymorphisms has been demonstrated in the vast majority of oral diseases [54][55][56] . In the current study, the T allele of the dnmt3b (C46359T) polymorphism was not associated with ED or p16 CDKN2A methylation status.…”
Section: Molecular and Clinical Factors And P16 Cdkn2a Methylationmentioning
confidence: 99%